2001
DOI: 10.1029/2000wr900273
|View full text |Cite
|
Sign up to set email alerts
|

Type curve interpretation of a cross‐hole pneumatic injection test in unsaturated fractured tuff

Abstract: Abstract. Cross-hole pneumatic injection tests have been conducted in 16 vertical and inclined boreholes in unsaturated fractured tuffs at the Apache Leap Research Site (ALRS) near Superior, Arizona. Their purpose was to characterize the bulk pneumatic properties and connectivity of fractures at the site on scales ranging from meters to several tens of meters. We describe the design, conduct, and type curve interpretation of one of these tests. Our cross-hole type curves are modified after Hsieh and Neuman [19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
99
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 71 publications
(104 citation statements)
references
References 33 publications
5
99
0
Order By: Relevance
“…We view the collection of all parameter estimates obtained in this manner, from the totality of pressure records, as a sample from a random population of equivalent log air permeabilities and log airfilled porosities representing nominal scales of meters to tens of meters. We expect them to be comparable to pneumatic parameters determined by Illman and Neuman [2001] on the basis of individual pressure records from test PP4 by means of analytically derived type-curves. All log air permeability estimates appear to be reasonable for a fractured tuff.…”
Section: Parametersmentioning
confidence: 79%
See 1 more Smart Citation
“…We view the collection of all parameter estimates obtained in this manner, from the totality of pressure records, as a sample from a random population of equivalent log air permeabilities and log airfilled porosities representing nominal scales of meters to tens of meters. We expect them to be comparable to pneumatic parameters determined by Illman and Neuman [2001] on the basis of individual pressure records from test PP4 by means of analytically derived type-curves. All log air permeability estimates appear to be reasonable for a fractured tuff.…”
Section: Parametersmentioning
confidence: 79%
“…The two sets of estimates are compared in Figure 5. Illman and Neuman [2001] concluded that a decrease in barometric pressure has no effect on estimates of k but causes the estimates of 4> to decrease by a factor of 1.1. We show in Appendix A that their conclusion, which is contrary to ours, stems from an artifact of their linearized analysis that is easy to eliminate.…”
Section: Parametersmentioning
confidence: 99%
“…In reality, we estimate these parameters from records of pressure variation with time in individual borehole intervals, one record at a time, by a numerical inverse procedure. This is akin in principle to interpreting each pressure record by the type curve method of Illman and Neuman [2001]. It yields a series of equivalent air permeabilities and air-filled porosities for rock volumes having length scales ranging from meters to tens of meters, represented nominally by radius vectors extending from the injection interval to the various monitoring intervals.…”
Section: Parameterization and Inverse Approachmentioning
confidence: 99%
“…Their purpose was to characterize the bulk pneumatic properties and connectivity of fractures at the site on scales ranging from meters to several tens of meters. The design, conduct, and type curve interpretation of one of these tests have recently been described by Illman and Neuman [2001]. The type curves they used have been modified after to consider single-phase airflow and extended to consider the effects of storage and skin in monitoring intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Illman and Neuman [2001] developed pressure and pressure derivative type curves for single-phase airflow. Illman [2005] analyzed the single-hole pneumatic injection and recovery tests for determining permeability, porosity, and skin.…”
Section: Introduction and Previous Studiesmentioning
confidence: 99%